Lula Rocha Anti-Racist Study Group - De Boni Silva, Lízia; Nery, Jônatas Corrêa; de Freitas Reis, Dilelcia; Berger, William; Sabará, Raquel (Guará Journal, 2025)
This article summarizes the trajectory of the Extension Pro-ject, Lula Rocha Anti-Racist Study Group (GEALR), linked to the Social Service Department of the Federal University of Espírito Santo (UFES) and the Center for Studies on Violence, Public Security and Rights Humans (NEVI). The Lula Rocha Anti-Racist Study Group aims to delve into the studies of the Ethnic-racial Question and build an agenda for valuing In-digenous-Afro-centered knowledge that articulates the aca-demic community, organized social movements, traditional peoples and communities and society in general. In 2023, the project won second place in the Maria Filina Award for Ex-tensionist Merit, Goiabeiras campus. The article presents the activities carried out in the first year of operation, as well as their objectives, methodology and results